2013
DOI: 10.1002/ajmg.a.36154
|View full text |Cite
|
Sign up to set email alerts
|

Neuromotor synapses in Escobar syndrome

Abstract: The Escobar variant of multiple pterygium syndrome (OMIM #265000) is a rare, autosomal recessive disorder associated with mutations in the γ-subunit of the nicotinic acetylcholine receptor (CHRNG). CHRNG is expressed in fetal muscle during motor development and contributes to the formation of neuromuscular junctions. Anomalies in neuromuscular junction structure and function have not been investigated in patients with Escobar syndrome. We report five patients identified as having Escobar syndrome, from four fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…Interestingly, patients with CHRNG ‐related nonlethal MPS display morphological abnormalities of the NMJ and non‐colocalization of NMJ proteins. Robinson et al previously reported a case where non‐colocalization of NMJ proteins was also detected (Robinson et al, ). These postnatal abnormalities at the NMJ probably reflect the developmental effects of impaired prenatal neuromuscular transmission as well as an aberrant neuromuscular synaptogenesis (Liu et al, ; Liu, Sugiura, Padgett, & Lin, ).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Interestingly, patients with CHRNG ‐related nonlethal MPS display morphological abnormalities of the NMJ and non‐colocalization of NMJ proteins. Robinson et al previously reported a case where non‐colocalization of NMJ proteins was also detected (Robinson et al, ). These postnatal abnormalities at the NMJ probably reflect the developmental effects of impaired prenatal neuromuscular transmission as well as an aberrant neuromuscular synaptogenesis (Liu et al, ; Liu, Sugiura, Padgett, & Lin, ).…”
Section: Discussionsupporting
confidence: 63%
“…The three criteria to be met by that papers in order to be eligible were: (a) patients with nonlethal MPS or ES, (b) detected CHRNG mutation/s, and (c) availability of sufficient clinical data of every patient. Ten papers with 57 cases met the established criteria (Al Kaissi et al, ; Bayram et al, ; Bissinger & Koch, ; Hoffmann et al, ; Kariminejad et al, ; Morgan et al, ; Robinson et al, ; Seo et al, ; Vogt et al, ). All cases collected are summarized in Table , Supporting Information Table S1, and Supporting Information Figure S1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings collectively suggest that features such as scoliosis and pterygia observed in individuals with DA8 likely have a different underlying molecular mechanism(s) than in recessive forms of MPS caused by mutations in the genes, CHRNG, CHRND, CHRNA1 9 , encoding subunits of the skeletal muscle nicotinic acetylcholine receptor (AChR). AChR is required for normal muscle development and muscle biopsies from individuals with recessive MPS have demonstrated abnormal distribution of AChR and acetylcholinesterase 29 . Since AChR is necessary for proper organization and establishment of the neuromuscular junction 30 as well as muscle and synaptic maturation 31 , it has been suggested that many features of recessive MPS such as the joint contractures and pterygia are ultimately caused by fetal akinesia 7 due to abnormal muscle and synaptic development.…”
Section: Figure 1 (Not Included)mentioning
confidence: 99%
“…9 Interestingly, several genes associated with NMJ have been implicated in this multiple pterygium syndrome (Escober type): CHRNA1, CHRNB1, CHRND, CHRNG, RAPSN, DOK7. 9,10 The severe, lethal form of multiple pterygium syndrome overlaps with fetal akinesia deformation sequence characterized by AMC, fetal akinesia, intrauterine growth restriction, pulmonary hypoplasia, several congenital anomalies, hydrops fetalis, and in utero death. 9 Homozygous mutations of CHRNA1 cause autosomal recessive lethal multiple pterygium syndrome.…”
Section: Discussionmentioning
confidence: 99%